Task-Based Budgeting - the Road to Effective Management of Public Finances - Adamczyk , Marcin (Studia Oeconomica Posnaniensia, 2013)
The purpose of this paper is to synthetically present the essence of taskbased budgeting and the notions of public finance management which are associated with it, as well as conducting a summary analysis of what has been achieved in recent years in terms of its implementation. This comes at a time when task-based budgeting, in addition to traditional budgeting, has become part of Poland’s public finances. The article also seeks answers to questions of what the new managerial approach to the management of public finances is and where it may lead; what the inherent weaknesses of the solutions connected with the new budgeting system may be; as well as what direction ought to be taken to ensure a proper management of public funds.